The possible influence of socio-cultural and socio-economic parameters on local languages: the case of Šalčininkai District - Čepaitienė, Agnė (Taikomoji kalbotyra, 2022)
The aim of the study is to use GIS tools and methods to identify the mobility trends of the members of the local communities of Šalčininkai district and surrounding areas and their impact on the local languages on the basis of socio-economic and socio-cultural parameters. The research material consists of: 1) survey data, on the basis of which the coefficients of the influence of attractions on the language were calculated; 2) statistical socio-economic data for 2020-2021; 3) geo-spatial data of Lithuania; 4) linguistic studies of Šalčininkai district. GIS tools and methods were used to assess the infrastructure of residential areas, a heat map of attractions with the greatest impact on linguistic shift was created based on the results of the survey, and a link network of Atlas of Lithuanian Language (ALL) points and infrastructures was implemented through accessibility analysis. Based on social network theory, the structure of socio-cultural networks and their influence on linguistic shift, as well as the influence of additional socio-economic and socio-cultural factors was assessed. The analysis has highlighted the linguistic, socio-economic and socio-cultural uniqueness of Šalčininkai district. The study area is a zone with a more internal mobility level: there is less migration between areas where different languages (Slavic and Lithuanian) are spoken, and more migration between different dialects (Eastern Aukštaitians of Vilnius and Southern Aukštaitians). However, due to the disappearance of ALL points in almost half of Šalčininkai district, the well-developed infrastructure in the district centre and the abundance of elderly communities in the district, the intensity of mobility is low. Therefore, all the areas surveyed can be considered socio-culturally non-isolated, but linguistically quite isolated. This ensures the survival and dominance of the Slavic language. The centre of the district – Šalčininkai (ALL 666) - is considered to be the most socio-economically and socio-culturally stable in the study area. However, this town attracts residents from socially unstable areas and residents of different dialects. This creates favourable socio-economic and socio-cultural conditions for the Slavic languages (partly also for Lithuanian dialects) to compete, but remain viable. The other ALL points in Šalčininkai district belong to the open zone, where the processes of shift in the characteristics of Slavic languages and/or Lithuanian dialects are taking place.
Keywords: sociocultural networks; GIS; Šalčininkai district; linguistic shift; geospatial analysis